Molecular Control of Sporophyte-Gametophyte Ontogeny and Transition in Plants - Pandey, Saurabh; Moradi, Amir Bahram; Dovzhenko, Oleksandr; Touraev, Alisher; Palme, Klaus; Welsch, Ralf (Frontiers in Plant Science, 2022)
Alternation of generations between a sporophytic and gametophytic developmental stage is a feature common to all land plants. This review will discuss the evolutionary origins of these two developmental programs from unicellular eukaryotic progenitors establishing the ability to switch between haploid and diploid states. We will compare the various genetic factors that regulate this switch and highlight the mechanisms which are involved in maintaining the separation of sporophytic and gametophytic developmental programs. While haploid and diploid stages were morphologically similar at early evolutionary stages, largely different gametophyte and sporophyte developments prevail in land plants and finally allowed the development of pollen as the male gametes with specialized structures providing desiccation tolerance and allowing long-distance dispersal. Moreover, plant gametes can be reprogrammed to execute the sporophytic development prior to the formation of the diploid stage achieved with the fusion of gametes and thus initially maintain the haploid stage. Upon diploidization, doubled haploids can be generated which accelerate modern plant breeding as homozygous plants are obtained within one generation. Thus, knowledge of the major signaling pathways governing this dual ontogeny in land plants is not only required for basic research but also for biotechnological applications to develop novel breeding methods accelerating trait development.